Demographic variability and density-dependent dynamics of a free-ranging rhesus macaque population - Hernández-Pacheco, Raisa (2013)
Density-dependence is hypothesized as the major mechanism of population regulation. However, the lack of long-term demographic data has hampered the use of density-dependent models in nonhuman primates. In this study, we make use of the long-term demographic data from Cayo Santiago’s rhesus macaques to parameterize and analyze both a density-independent and a density-dependent population matrix model, and compare their projections with the observed population changes. We also employ a retrospective analysis to determine how variance in vital rates, and covariance among them, contributed to the observed variation in long-term fitness across different levels of population density. The population exhibited negative density-dependence in fertility and the model incorporating this relationship accounted for 98% of the observed population dynamics. Variation in survival and fertility of sexually active individuals contributed the most to the variation in long-term fitness, while vital rates displaying high temporal variability exhibited lower sensitivities. Our findings are novel in describing density-dependent dynamics in a provisioned primate population, and in suggesting that selection is acting to lower the variance in the population growth rate by minimizing the variation in adult survival at high density. Because density-dependent mechanisms may become stronger in wild primate populations due to increasing habitat loss and food scarcity, our study demonstrates it is important to incorporate variation in population size, as well as demographic variability into population viability analyses for a better understanding of the mechanisms regulating the growth of primate populations.